The Relation between the CSR and the Accounting Information System Data in Central and Eastern European (CEE) Countries – The Evidence of the Polish Financial Institutions - Justyna Fijałkowska; Beata Zyznarska-Dworczak; Przemysław Garsztka (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Financial institutions play a fundamental role in determining the sustainability of economies, both in developed and developing countries. However, the worldwide financial crises made many financial institutions lost their credibility and CSR engagement has been perceived as a remedy. The aim of this paper is to analyze the interrelation between being socially responsible and tangible financial outcome of financial institutions in one of the CEE countries - Poland. Financial and market data of all the public companies from the financial sector in Poland – 116 financial institutions. The analyzed period is 2012-2015 that gives 257 observations. The empirical results reveal that in case of financial institutions in Poland the slack resources are strongly related to CSR involvement, however being socially responsible is not reflected in the bottom line. Polish market and the public are reluctant in considering the CSR importance and the CSR engagement is not rewarded. This undermines the role of CSR commitment in financial institutions in CEECs. It may be assumed that CSR efforts in Poland are not focused properly, or they are not communicated effectively. On the basis of comparative analysis is presented there is a significant difference between CEE countries and other transitional countries in CSR implementation and communication. The findings are important in better understanding of the link between CSR engagement and its tangible outcomes in CEE countries. The conclusions may lead to the improved decision-making processes concerning CSR activities and their communication.
Keywords: M14; M40; M41; Q56; 650; CSR; financial performance; financial institutions; banks; Central and Eastern Europe; CEE; CEE countries